2010
DOI: 10.1038/onc.2010.60
|View full text |Cite
|
Sign up to set email alerts
|

Multiple receptor tyrosine kinases regulate HIF-1α and HIF-2α in normoxia and hypoxia in neuroblastoma: implications for antiangiogenic mechanisms of multikinase inhibitors

Abstract: Novel treatment approaches are needed for children with advanced neuroblastoma. Studies with neuroblastoma cells have indicated the presence of a hypoxiadriven vascular endothelial growth factor (VEGF)/VEGF receptor (VEGFR)-1 autocrine loop modulating hypoxiainducible factor-1alpha (HIF-1a). Whether other receptor tyrosine kinases (RTKs) are capable of modulating HIF1a levels and whether RTKs can regulate HIF-2a as well is largely unknown. We evaluated neuroblastoma cell lines for expression of various RTKs. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 46 publications
6
51
1
Order By: Relevance
“…14, 15). While the blocking of VEGFR and PDGFR may account for the antiangiogenesis effect of sorafenib in HCC, sorafenib, and sunitinib can also inhibit the expression of HIF-1a in neuroblastoma and colon cancer cells (16,17). These findings may suggest the potential role of HIF-1a in mediating antiangiogenesis effect of sorafenib in HCC.…”
Section: Introductionmentioning
confidence: 63%
“…14, 15). While the blocking of VEGFR and PDGFR may account for the antiangiogenesis effect of sorafenib in HCC, sorafenib, and sunitinib can also inhibit the expression of HIF-1a in neuroblastoma and colon cancer cells (16,17). These findings may suggest the potential role of HIF-1a in mediating antiangiogenesis effect of sorafenib in HCC.…”
Section: Introductionmentioning
confidence: 63%
“…It is suggested that both PI3K and MAPK pathways can mediate this phenomenon [167]. The crosstalk between RET and HIF-1α has been described also in neuroblastoma cells, where activation of RET induced by its ligand GDNF increases HIF-1α protein levels [130]. In turn, expression of GDNF was reported to be increased in hypoxic rat astrocytes [168].…”
Section: Pdgfr Fgfr and Retmentioning
confidence: 97%
“…Recent studies using neuroblastoma cells indicated that VEGF-induced activation of VEGFR-1 leads to increase of both HIF-1α and HIF-2α protein levels [130]. In clinical neuroblastoma specimens, HIF-2α protein levels positively correlate with VEGF expression and poor patient outcome [131].…”
Section: 2vegfrmentioning
confidence: 99%
See 1 more Smart Citation
“…The approval of sorafenib, a Raf inhibitor and anti-angiogenic agent, as single agent against HCC probably demonstrates this principle. Although, the effect of sorafenib on HIF-1 activity has not been directly studied in HCC, sorafenib has been shown to interfere with the HIF pathway in models of melanoma and neuroblastoma (Kumar et al, 2007;Nilsson et al, 2010). It is possible that combination of sorafenib with other agents that also target ERK (such as kaempferol or other naturally occurring substances with similar properties), HIF-1 (such as MTD) or VEGF (such as bevacizumab or inhibitors of the VEGF receptor) could be more efficient in treating HCC and preventing acquirement of resistance (Fig.…”
Section: Targeting the Hif Pathway In Hccmentioning
confidence: 99%